Studi Beton Dari Limbah Batu Alam Untuk Percepatan Rekonstruksi Hunian Pasca Bencana - Dimas Langga Chandra Galuh; Lilik Hendro Widaryanto; M. Afif Shulhan (RENOVASI : Rekayasa Dan Inovasi Teknik Sipil, 2019)
The country of Indonesia is in a disaster-prone area so that it has a high potential for natural disasters, which can cause damage to buildings. Innovations are needed in handling disasters from both structural and material aspects so that they can accelerate the reconstruction phase.This study will conduct a study of the use of local materials in the form of temple natural stone waste as coarse aggregates on concrete. Addition of additive material to the mixture is used to achieve high early strength.The required concrete strength (f'c) = 19.3 MPa with the composition for one concrete cylinder consists of water: cement: sand: temple natural stone waste: additive material with a mixture of 1.2 liters: 1.9 kg: 3 , 6 kg: 5.2 kg: 20 ml. The results of testing the concretestrength with the addition of additive materials at the age of 3 and 7 days were 16.04 MPa and 23.02 MPa. The percentage of compressive strength of concrete at the age of 3 days is 83.1%, whereas at the age of 7 days it has exceeded the required concrete compressive strength (119.3%). Based on this study, the use of local materials in the form of temple natural stone waste with the addition of 7-day-old concrete additives can replace broken stone material in the disaster reconstruction process.